DAMPAK RASIO KEUANGAN, PASAR SAHAM, DAN NILAI TUKAR PADA RETURN SAHAM INDOCEMENT TUNGGAL PRAKARSA - Grace Orlyn Sitompul; Jhon Rinendy (POLITEKNIK LP3I JAKARTA, 2024)
The objective of this research is to analyze the impact of financial ratios, namely (Current Ratio, Return On Assets, Total Asset Turnover, Debt to Assets Ratio), Stock Market, and Exchange Rate over the period from 2012 to 2022. The sample selection was conducted purposively on Indocement Tunggal Prakarsa (LQ45) stocks, which consistently had annual financial reports during the period, resulting in 44 quarterly samples. Partial and simultaneous multiple linear regression tests were used in this study. Empirical evidence indicates that Total Asset Turnover (TAT) and the Stock Market have a positive and significant effect on stock returns, while the Current Ratio (CR), Return On Assets (ROA), and Exchange Rate do not have a significant impact. Conversely, the Debt to Assets Ratio (DAR) has a negative impact on LQ45 stock returns. Overall, Liquidity, Profitability, Activity, Leverage, Stock Market, and Exchange Rate collectively have a positive and significant influence on Stock Returns.